Um estudo comparativo de procedimentos de análise estrutural para torres eólicas de concreto armado - Barroso Filho, Nertan Fonseca (2018)
The study of economic solutions for wind turbine structures has attracted interest due to the environmental appeal of this renewable energy source. Particularly, steel wind towers have been well studied both in terms of analysis and structural optimization. In general, the consumption of material that is directly related to the cost is minimized. However, limitations in the dimensions due to transport have been an important factor for the use of reinforced concrete towers. In optimization, a critical step is the process of analysis. In the analysis, we generally seek answers in terms of resistance, stability, rigidity and fundamental frequency. Modern computational resources have allowed the application of refined numerical structural analysis procedures. However, using these features in an optimization model can make the process computationally expensive. The use of substitute models has been well studied, but an alternative is the adoption of simplified procedures, generally conservative, and much used in preliminary projects. The wind tower considered in this work is 100 m high with a turbine of 3.6 MW, whose actions were obtained from the literature. In this work, we intend to study and compare models of analysis of wind-powered reinforced concrete towers. The models will be compared through finite element methods with consideration of one-dimensional and two-dimensional finite elements. Wind modeling along the tower will be treated as static. The influence of physical and geometric nonlinearities, soil-structure interaction and their effect on the tower natural frequencies and its displacements, as well as its natural frequencies will be evaluated. The beam model is validated for application in optimization models.